Distress tolerance dimensions and smoking behavior among Mexican daily smokers: A preliminary investigation. (June 2017) - Kauffman, Brooke Y.; Garey, Lorra; Bakhshaie, Jafar; Rodríguez, Rubén; Cárdenas, Samuel Jurado; Coy, Patricia Edith Campos; Zvolensk, Michael J.
Abstract: Introduction: Distress intolerance has been implicated in various aspects of smoking maintenance and quit behavior, although past work has been conducted almost exclusively among European American samples. Method: The present study sought to extend past work by exploring distinct subdimensions of distress tolerance (Tolerance, Appraisal, Regulation, and Absorption) among a sample of 113 (53.1% female; M age = 22.81, SD = 2.13) adult daily smokers from Mexico City, Mexico in regard to multiple indices of problematic smoking. Results: Results indicated that the Appraisal dimension of distress intolerance was associated with smoking more cigarettes per day, a greater number of (lifetime) failed quit attempts, and an increased likelihood of early smoking relapse. These findings remained significant after controlling for negative affectivity, gender, alcohol usage as well as the variance accounted for by other distress tolerance dimensions. Conclusions: Such results provide novel preliminary empirical evidence that lesser perceived ability to tolerate distress because it is appraised as 'unacceptable' may be a particularly important element of the construct in terms of better understanding multiple public health relevant indicators of smoking for Mexican smokers. Overall, the present findings uniquely contribute to a growing body of research related to distress intolerance and its implications for explicating the nature of the maintenance of smoking behavior among a highly understudied segment of the smoking population (Mexican smokers). Highlights: Appraisal dimension of perceived distress intolerance was associated with smoking more cigarettes per day. Appraisal dimension of perceived distress intolerance was associated with a greater number of failed quit attempts. Appraisal dimension of perceived distress intolerance was associated with increased likelihood of early smoking relapse. Results were examined in a highly understudied segment of the smoking population (Mexican smokers).